Public perception of air quality in Aceh District’s border areas - Fazira, Aulya; Kiswanto, Kiswanto; Siahaan, Perry Boy Chandra; Murdani, Ihsan; Saputra, Firman Firdauz (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
Climate change and industrial activities have contributed to a decline in air quality in the border region between Aceh Barat and Nagan Raya Districts, adversely affecting public health, particularly through increased cases of Acute Respiratory Infections (ARI). This study aims to analyze community perceptions of air quality in this area. A qualitative approach was employed, utilizing in-depth interviews with residents of border villages who were purposively selected based on criteria including a minimum of five years of residency, experience of health impacts, and involvement in community activities. Data collection was supplemented by field observations and secondary documents obtained from relevant agencies. The findings indicate that local communities experience direct effects of air pollution, such as exposure to dust, eye irritation, and respiratory problems, especially during the dry season and periods of increased heavy vehicle activity. However, official government monitoring remains limited and does not include measurements of fine particulate matter (PM2.5 and PM10), resulting in a gap between technical data and community experiences. Residents also noted a lack of public awareness campaigns addressing the health risks associated with air pollution. The study concludes that community-based approaches and data transparency are essential for effective air quality management. A key policy recommendation is the adoption of a hybrid air monitoring system that integrates technical measurements with community-reported experiences, thereby informing more responsive environmental and public health interventions.